Stroke or left atrial thrombus prediction using antithrombin III and mean platelet volume in patients with nonvalvular atrial fibrillation - Choi, Seo‐Won (Clin Cardiol, 2017)
BACKGROUND: CHADS(2) (congestive heart failure, hypertension, age ≥ 75 years, diabetes mellitus, stroke) and CHA(2)DS(2)‐VASc (congestive heart failure, hypertension, age ≥ 75 years, diabetes mellitus, stroke, vascular disease, age 65 to 74 years, sex category) scores showed just moderate discrimination ability in predicting thromboembolic complications in patients with nonvalvular atrial fibrillation (AF). HYPOTHESIS: To determine the association of antithrombin III (AT‐III) deficiency and mean platelet volume (MPV) with the development of stroke or left atrial (LA) thrombus in patients with AF. METHODS: AT‐III and MPV were analyzed in 352 patients with AF. The primary endpoint was a composite of ischemic stroke event and incidental LA thrombus. RESULTS: There were 50 events (14.2%) during a mean 35.4 months of follow‐up. A significantly higher stroke or LA thrombus rate was observed in the low–AT‐III group (<70%) than that in the high–AT‐III group (≥70%). A significantly higher stroke or LA thrombus rate was observed in the high‐MPV group (≥7.0 fL) than that in the low‐MPV group (<7.0 fL). AF patients with an MPV ≥7.0 fL and AT‐III deficiency had higher stroke or LA thrombus risk than those without an MPV ≥7.0 fL and AT‐III deficiency. In the Cox proportional hazard analysis, high MPV was found to be an independent predictor of stroke or LA thrombus risk (hazard ratio: 6.408; 95% confidence interval: 2.874‐14.286). Although AT‐III deficiency was not an independent predictor of stroke or LA thrombus risk, a trend was observed. CONCLUSIONS: High MPV and AT‐III deficiency were predictive markers for stroke or LA thrombus. Their predictive power for stroke was independent of antiplatelet treatment, anticoagulation therapy, and a high CHA(2)DS(2)‐VASc score in patients with AF.